2021
DOI: 10.5114/reum.2021.112351
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression are common in rheumatoid arthritis and correlate with poor quality of life in Indian patients

Abstract: Objectives: We planned this study to assess the prevalence of anxiety and depression in rheumatoid arthritis (RA) patients and its correlation with quality of life (QOL) in these patients. Material and methods: Eighty-eight patients (76 females) were included in this cross-sectional study. The Hospital Anxiety and Depression Scale (HADS) was used to assess anxiety and depression. Quality of life was measured using the World Health Organization WHOQOL-BREF. The severity of pain was measured by 100-millimetre-lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
(48 reference statements)
1
6
0
Order By: Relevance
“…Several studies from Egypt, India, Iran, and China showed high depression and anxiety levels in RA patients. 11, 37 - 39 In a review study, Gettings 40 analyzed the RA-associated psychological impact and assumed that disease-related disabilities, pain during disease activity, and other social difficulties plausibly explain the high anxiety and depression levels in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies from Egypt, India, Iran, and China showed high depression and anxiety levels in RA patients. 11, 37 - 39 In a review study, Gettings 40 analyzed the RA-associated psychological impact and assumed that disease-related disabilities, pain during disease activity, and other social difficulties plausibly explain the high anxiety and depression levels in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…In detail, RA patients have to face many obstacles during routine daily life owing to unbearable pain, joint deformity, fatigue, diet, etc. Owing to the incurability of RA, these RA patients are always under high psychological pressure, which vastly increases their risk of anxiety and depression [ 12 , 16 , 25 ]. The increased financial disbursement for anxiety and depression could, in turn, aggravate RA by reducing the expense for RA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous papers have reported that anxiety and depression are highly prevalent in RA patients, indicating that the anxiety rate might even be as high as 69.6% and the depression rate as high as 14–58.3% [ 10–15 ]. Meanwhile, other studies have observed that anxiety or depression is related to pain degree, quality of life, and sleep disturbance in RA patients [ 16 , 17 ]. However, previous studies have applied only a single scale to evaluate anxiety and depression, and the independent risk factors related to their occurrence have seldom been investigated; moreover, the consistency between different scales in RA patients has also not been reported sufficiently.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is substantial literature available concerning neuropsychiatric conditions and inflammatory diseases. RA has been associated with an increased risk of developing anxiety and major depressive disorder [268][269][270]. In SLE, neuropsychiatric symptoms have long been recognized in the American College of Rheumatology diagnostic guidelines [13].…”
Section: Neuropsychiatric Phenomena In the Context Of Chronic Periphe...mentioning
confidence: 99%